Industrial Organization - Burgess H. Giles Jr (Prentice Hall, 1989)
This text will guide the student to understanding why ''real world'' markets are organized as they are and why they behave as they do. Preface, An Introduction to Industrial Organization, The Market, The Firm, Industrial Organization, Market Structure, Economies of Scale and Barriers to Entry, Market Concentration, Product Differentiation, Market Structure and Performance, Market Strategy, Oligopoly Pricing: The Theory, Oligopoly Pricing: Mechanisms of Cooperation, Pricing Independence in Monopoly and Oligopoly, Competition in Selling Efforts: Advertising and Related Market Behavior, Competition in Product Efforts: Innovation and Related Market Behavior, The Managerial Firm: Organization and Strategy, The Dynamics of Structure and Strategy, Antitrust Policy, Maintaining Competition: The Sherman Act, Protecting Competition: The Clayton Act, Index.